PELATHAN KADER RW SIAGA SEHAT JIWA DI WILAYAH KERJA PUSKESMAS CIGEUREUNG KECAMATAN CIPEDES KOTA TASIKMALAYA - Ridwan Kustiawan; Peni Cahyati; Dudi Hartono; Asep Riyana (Jurnal Pengabdian Masyarakat DEDIKASI, 2020)
The process of community empowerment in this case mental health cadres who have a role in moving the community in following counseling on mental health is very important, considering that in the community there are many sources that can cause families to experience mental health risks or disorders in addition to maintaining their health conditions. Mental health cadres are expected to be able to provide knowledge to the public about the mental problems faced by them. Through this training activity, the basic skills possessed by cadres regarding early detection of mental health, education about mental health are increased. This will go hand in hand with the active participation of health care workers, in this case the Puskesmas nurses. The mental health cadre training was attended by 42 cadres at the Cigeureung Community Health Center. Based on the results of the pretest and post-test, the score increased by 16 points (9.2%), meaning that there was an increase in cadres' knowledge of mental health. In addition, cadres can detect mental health early through simulations in families and communities